Purification and Characterization of a Low Molecular Weight Neutral Non-Starch Polysaccharide from Panax ginsen g by Enzymatic Hydrolysis - Ying Ying; Chao Ma; Yajie Zhang; Xiaoping Li; Hongxin Wu (Polish Journal of Food and Nutrition Sciences)
In this study, a novel neutral non-starch polysaccharide (GP1A) was extracted using hot water from ginseng roots. Chemical characteristics, monosaccharide compositions and structure of GP1A were investigated using scanning electron microscopy, gel permeation chromatography, X-ray diffraction, Fourier transform infrared spectroscopy, gas chromatography with mass spectrometer, one-dimensional and two-dimensional nuclear magnetic resonance. The results indicated that the lyophilized GP1A was a homogeneous polysaccharide with a low molecular weight of 1.03 kDa. The dominating monosaccharides of GP1A were D-glucose, D-galactose, D-mannose, D-xylose and D-arabinose. The structure analysis indicated the main chain residues sequence of GP1A was α-D-Glc p -(6→3)-α-D-Gal p -(1→1)-α-D-Glc p -(3→4)-β-D-Man p -(2→2)-β-D-Ara p with branch chains of α-D-Glc p substituted at α-D-Gal p and β-D-Xyl p substituted at β-D-Manp.